Methodological aspects of evaluation of the enterprise’s internal control by the auditor - Dorosh, N. I.; Fesai, M. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article is devoted to the methodology for assessment of the internal control system at the enterprise by auditors, by addressing the following tasks: to determine the role of assessment of the internal audit at the enterprise in the auditing of financing reporting; to define business processes at the enterprise and the method for detecting the risks of essential distortions of risk-related information, and embed the means of control in the overall organization structure; to sum up the testing techniques involved in the internal control at the enterprise by showing the essence of testing for the adequacy of development and effectiveness of operation of the internal control at the enterprise; to show the impact of assessment of the internal control at the enterprise on the planning of auditor procedures in substance. Issues dealt with in the study include phases of financial reporting audit by business process, classification of types of control at the enterprise, the need to distinguish between the test for the adequacy of development of internal control and the test for the effectiveness of operation of the internal control etc. The auditor’s actions in detecting deviations from the internal control system established at the enterprise are illustrated. The conclusion is made that a properly organized auditing of the internal control at the enterprise and well-designed techniques of control enable for quick detecting of errors and drawbacks of the internal control and take relevant measure for their prevention.